Nanoparticle assorted biofuels production from biowastes through transesterification. (1st January 2023) - Sathish, T.; Saravanan, R.; Rajasimman, M.; Ghfar, Ayman A.; Ramkumar, Vanaraj
Highlights: Extracted Biofuel from the bio waste of Chicken shop by transesterification process. Extracted Chicken waste oil (Biofuel) was enhanced with ZnO Nanoparticles. BCW20/200ZnO Nanofuel exhibited 25% higher BTE than pure Diesel. BCW20/100ZnO Nanofuel exhibited 13% higher BTE than pure Diesel. SFC of BCW20/200ZnO and BCW20/100ZnO are 4% & 1% lesser than diesel. Abstract: Microbial engineering is a new class of engineering that integrates the technologies of developing alternate fuels with chemical engineering and biotechnology. Clean technology-based research creates a high social impact and offers high benefits to society. This manuscript addresses the utilisation of biowaste from chicken shops for generating biofuel through transesterification and preparing Nano-fuels. The extracted biofuel was considered for preparing the B20 grade biodiesel, the biodiesel enhanced by mixing of ZnO nanoparticles (Nano-fuels). Through Ultrasonicator the B20 grade biodiesel mixed with ZnO (Zinc Oxide) Nanoparticles (50 Nano-meter (nm) average-sized) at two different concentrations. The proposed fuels like BCW20 biodiesel (20 %Chicken biowaste oil and 80 % Diesel), Nano-fuels (concentrations of 100 parts per million (ppm) and 200 ppm of ZnO nanoparticles) and tested these fuels in diesel engines to ensure its compatibility. The performance above said fuels were compared in terms of Brake Thermal Efficiency (BTE) and Brake Specific Fuel Consumption (BSFC), combustion performance by In-cylinder Pressure (ICP) and Heat Release Rate (HRR), and emission performance by emission of nitrogen oxides (NOx), Hydrocarbons (HC) and Carbon monoxide (CO). The comparative analysis revealed that 200 ppm ZnO nanoparticles concentrated Nano fuel outperformed by yielding 27 % higher BTE, proved economy by 4 % lesser BSFC, and also reduced NOx, HC, and CO emissions by 17 %, 7 %, and 11 %, respectively. The best operating condition is the use of BCW20 + 200 ZnO fuel, in particularly above 3.5KW of brake power (BP), the BSFC recorded less, at above 75 % load HC emissions found less and remaining other aspects there is no limitation in the use of recommended BCW20 + 200 ZnO fuel.